MIDDLE PLIOCENE SMALL MAMMALS OF THE RUSSIAN PLAIN - Agadzhanyan A.K. (My University, 2003)
Materials on small mammals collected during last years enable discrimination of an autonomous Uryv faunal assemblage in the Pliocene succession of mammal communities of the Russian Plain. Data on taphonomy and compositional peculiarities of the assemblage are considered. Evolutionary transformations in communities of the Uryv fauna are established. The fauna evolutionary period corresponds to Zone 16 by P. Mein and spans the greater middle and basal upper Pliocene.
Keywords: Pliocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен